Angus, thongs and full-frontal snogging - Rennison, Louise (Avon Books, 2003)
Presents the humorous journal of a year in the life of a fourteen-year-old British girl who tries to reduce the size of her nose, stop her mad cat from terrorizing the neighborhood animals, and win the love of handsome hunk Robbie.